Characterization of reduced graphene oxide conductive polymer composites towards the development of non-invasive glucose biosensors - Habibah Farhana binti Abdul Guthoos (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Graphene and conductive polymers had gain great deal of interest in various fields, such as in energy, environmental, and biomedical application, owing to their outstanding chemical and physical properties compared to conventional metal. Thus, in this study a reduced graphene oxide (rGO)-poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS)-based electrode was fabricated via a simple two-step, physical drop-cast method followed by subsequent electrochemical reduction. Cyclic voltammetry (CV) was used to characterize the redox capability of the composite layer on the electrode surface. Electrochemical deposition of rGO-PEDOT:PSS composites with a 1:1 ratio gives the highest anodic peak current Ipa of 1.184 mA and the largest effective surface area of 12.9 mm2, compared to rGO alone electrodes (Ipa = 0.552 mA, A=12.9 mm2). The rGO-PEDOT:PSS composites were characterized by scanning electron microscopy (SEM), transmission electron microscope (TEM), RAMAN Spectroscopy, Fourier-transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD). SEM results show the composite to have an open edge with a rougher surface morphology compare to rGO alone and TEM implies PEDOT:PSS is encapsulated by rGO. RAMAN spectroscopy shows the D band/G band intensity ratio of the composite films was increased from 1.12 (GO-PEDOT-PSS) to 1.25 (rGO-PEDOT:PSS) after electrochemical reduction, suggesting reduction of defects in graphene. Furthermore, XRD shows that the interlayer distance of rGO was increased from 0.37 nm (for rGO film) to 0.47 nm for rGO-PEDOT-PSS, confirming the effective intercalation of PEDOT/PSS in between rGO layers. Finally, glucose biosensor with rGO-PEDOT:PSS as transducer was successfully fabricated, and the sensitivity, sensitivity per electrode area, and limit of detection were 2.03 µA/mM, 15.74 µA/mM cm2, and 0.08 µM, respectively. The results show rGO-PEDOT:PSS composite is an excellent precursor for the development of redox active transducer that can result in highly sensitive non-invasive glucose sensor. Keywords: graphene, reduced graphene oxide, cyclic voltammetry, PEDOT:PSS, glucose sensor